2013
DOI: 10.7150/ijms.5123
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced MR Imaging in a Phase Ⅱ Study on Neoadjuvant Chemotherapy Combining Rh-Endostatin with Docetaxel and Epirubicin for Locally Advanced Breast Cancer

Abstract: Background: Anti-angiogenesis is a promising therapeutic strategy for locally advanced breast cancer. We performed this phase II trial to evaluate the anti-angiogenesis and anti-tumor effect of rh-endostatin combined with docetaxel and epirubicin in patients with locally advanced breast cancer by dynamic contrast-enhanced magnetic resonance imaging in 70 previously untreated locally advanced breast cancer patients.Methods: The study population was randomly assigned to neoadjuvant chemotherapy with docetaxel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Jia et al found that rh-endostatin inhibited angiogenesis of breast cancer, indirectly leading to tumor regression and dormancy [ 42 ]. The study also found that the combination of rh-endostatin in breast cancer can potentiate the anti-tumor effect of the neoadjuvant chemotherapy, and exacerbate tumor regression.…”
Section: Clinical Utility Of Rh-endostatin In Cancer Treatmentmentioning
confidence: 99%
“…Jia et al found that rh-endostatin inhibited angiogenesis of breast cancer, indirectly leading to tumor regression and dormancy [ 42 ]. The study also found that the combination of rh-endostatin in breast cancer can potentiate the anti-tumor effect of the neoadjuvant chemotherapy, and exacerbate tumor regression.…”
Section: Clinical Utility Of Rh-endostatin In Cancer Treatmentmentioning
confidence: 99%
“…for the treatment of non-small-cell lung cancer in combination with vinorelbine-cisplatin (phase III trial [208]). Several phase I [209,210], and II [211][212][213][214][215][216][217][218][219] clinical trials have been conducted these last five years in patients with melanoma [213], nasopharyngeal carcinoma [215], head and neck carcinoma [218] lung [211,216,217,219,220], pancreatic [209],…”
Section: Ecm Bioactive Fragments As Drugs and Biomarkersmentioning
confidence: 99%
“…As a result, non-invasive imaging modalities are being evaluated to predict patients likely to respond early in their therapy as a method of delivering personalized therapeutic cancer therapy (6–8). Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has been evaluated to assess early tumor response following chemotherapy (911) or XRT (1214). DCE-MRI can retrieve pharmacokinetic parameters of an MR contrast agent in a target tissue monitoring the dynamic change of contrast concentration over time (15).…”
Section: Introductionmentioning
confidence: 99%
“…DCE-MRI can retrieve pharmacokinetic parameters of an MR contrast agent in a target tissue monitoring the dynamic change of contrast concentration over time (15). Effective killing of cancer cells alters microvasculature in a tumor, represented by the change of K trans (forward volume transfer constant: wash-in rate) values that are quantifiable from DCE-MR images (11,14). The early assessment of tumor response may improve clinical outcomes by discontinuing a failing treatment in a timely manner.…”
Section: Introductionmentioning
confidence: 99%